KOMPETENSI ABSOLUT PENGADILAN HUBUNGAN INDUSTRIAL JAKARTA PUSAT BERDASARKAN KLAUSULA ARBITRASE (PUTUSAN: 247/PDT.SUS-PHI/2019) - Sunita Caroline Pontoh; Andari Yurikosari (Fakultas Hukum Universitas Trisakti, 2022)
PT Harry Sangari, the defendant, failed to pay him his salaries. Phillip Sekuritas Indonesia because the employment contract between the plaintiff and the defendant has an arbitration clause that impairs the Industrial Relations Court's unqualified authority. This research focuses on Decision 247/Pdt.Sus-PHI/2019. Deals with the topic what is the analysis of the decision made by the panel of judges of the Industrial Relations Court Central Jakarta in deciding dispute number 247/Pdt.Sus-PHI/2019 regarding the arbitration clause in a cooperation agreement, and how is the absolute competence of the Central Jakarta Industrial Relations Court in examining and deciding disputes on rights based on the arbitration clause in the cooperation agreement based on statutory regulations. This research is normative, descriptive, using primary and secondary data, qualitatively analyses, with a deductive method. It can be concluded that the industrial relations court does not have the authority to decide on the case because the procedural law that applies to the parties is the civil procedural law contained in the civil code. Analysis of the Decision Number 247/PDT.SUS-PHI/2019 is not in accordance with Article 50 of Law Number 48 of 2009 concerning Judicial Power so that the decision is included in the wrong an unreasonable decision.